Einfluß einer dreidimensionalen Datenstabilisierung in der Radionuklidventrikulographie auf den statistischen Zählfehler der Ejektionsfraktion - Mester, J.; Clausen, M.; Henze, E.; Ochsenkühn, R.; Lietzenmayer, R.; Weller, R.; Adam, E.W. (Nuklearmedizin - NuclearMedicine, 1990)
The suitability of a 3-dimensional filter in diminishing the statistical noise of left ventricular volume curves without any systematical error in the left ventricular ejection fraction (EF) was investigated. The EF values were compared in 50 studies on 24 patients. There was no significant systematical difference between the EFs before and after filtering. The filter diminishes the statistical uncertainty of the EF by a factor of 0.47. Therefore, the method may possibly be employed in processing the left ventricular volume curves.